RULE OF LAW, FREEDOM AND DEMOCRACY. THE POLITICAL THOUGHT OF DON FRANCISCO ZARCO AFTER THE FALL OF THE EMPIRE (1867-1869) (Tzintzun, Revista de Estudios Históricos, 2022)
This article focuses on the use and meaning that Francisco Zarco assigned to some of the key concepts of his political thought during the last two years of his life. For this, the articles published during this period in El Siglo Diez y Nueve were analyzed, paying special attention to the historical circumstances in which they were written. The objective is to delve into the richness and complexity of the political thought of the intellectual from Durango, in order to understand his contributions, not only to the prevailing liberalism of the time, but also to other ideological corpus, such as democracy and republicanism.
Keywords: Francisco Zarco; political thought; liberalism; republicanism; democracy